Review Of The Effect Of Yttrium And Neodymium On Microstructure And Mechanical Properties Of Magnesium Alloy - MOHD AZHAR, NOOR ARWANI SYAFIRA; AHMAD, ROSLI (Research Progress in Mechanical and Manufacturing Engineering, 2022)
The use of magnesium alloys in the manufacturing, automotive, and aerospace industries has led to research to investigate the effects of rare earth elements on these materials. The impact of the rare earth elements yttrium (Y) and neodymium (Nd) on the microstructure and mechanical properties of the magnesium alloy was investigated in this research. By referring to past research and academic publications, the case study method was used. In the selected references, from the experiments that were conducted using optical microscopy (OM), scanning electron microscopy (SEM) coupled with electron dispersive spectroscopy (EDS), the tensile test and Vickers Hardness test showed that the addition of yttrium and neodymium in different amounts improved the grain size and volume fraction, Ultimate Tensile Strength and hardness value of the magnesium alloys. Both additives improve the microstructure and mechanical properties of magnesium alloys, but different types of magnesium alloys have different compositions, which makes the optimum weight percentage of yttrium and neodymium additions differ too.